Cellular response to persistent foot-and-mouth disease virus infection is linked to specific types of alterations in the host cell transcriptome - Han, Lingling (Sci Rep, 2018)
Food-and-mouth disease virus (FMDV) is a highly contagious virus that seriously threatens the development of animal husbandry. Although persistent FMDV infection can dramatically worsen the situation, the mechanisms involved in persistent FMDV infection remain unclear. In the present study, we identified the presence of evolved cells in the persistently FMDV-infected cell line. These cells exhibited resistance to the parent FMDV and re-established persistent infection when infected with FMDV-Op (virus supernatant of persistent infection cell lines), emphasizing the decisive role of evolved host cells in the establishment of persistent FMDV infection. Using RNA-seq, we identified the gene expression profiles of these evolved host cells. In total, 4,686 genes were differentially expressed in evolved cells compared with normal cells, with these genes being involved in metabolic processes, cell cycle, and cellular protein catabolic processes. In addition, 1,229 alternative splicing events, especially skipped exon events, were induced in evolved cells. Moreover, evolved cells exhibited a stronger immune defensive response and weaker MAPK signal response than normal cells. This comprehensive transcriptome analysis of evolved host cells lays the foundation for further investigations of the molecular mechanisms of persistent FMDV infection and screening for genes resistant to FMDV infection.